PENGARUH BRAND EXPERIENCE TERHADAP BRAND EQUITY MELALUI COSTUMER COMMITMENT DAN CUSTOMER SATISFACTION PADA KEDAI KOPI ZXC DI SURABAYA - Walukow, Verby Stevan; Ellitan, Lena; Suhartatik, Ani (Universitas Katolik Widya Mandala Surabaya, 2021)
Today's business competition is unavoidable along with themore innovative business people and the development of technology.One of the competitive advantages that every business person wants togain is a good brand experience. A good brand experience will providesatisfaction for customers which in turn will provide additional valuefor a brand. This study aims to analyze the effect of brand experience onbrand equity by considering customer commitment and customersatisfaction at Surabaya Town Square. Quantitative methods are usedin conducting research based on primary data. A total of 150respondents who became the research sample using a samplingtechnique using purposive sampling. In conducting the analysis usingthe SEM approach using the help of the SmartPLS program. The resultsof this study indicate that there is a significant positive effect betweenbrand experience on customer commitment and satisfaction, but doesnot have a significant effect on brand equity; There is no positive effectbetween customer commitment and brand equity; but there is a positiveeffect between customer commitment and brand equity